Systematic literature review on critical thinking in higher education - Rothinam, Nirumala; Vengrasalam, Rama; Naidu, Sivabala; Nachiappan, Suppiah; Jabamoney, Samikannu (Edelweiss Applied Science and Technology, 2025)
The purpose of this paper is to conduct a comprehensive systematic literature review (SLR) on the development, assessment, and influencing factors of critical thinking in higher education. As critical thinking is widely recognized as a core competency for academic and professional success, this review aims to synthesize empirical evidence on how it is fostered across various disciplines and learning environments. The study investigates effective pedagogical strategies, assessment techniques, and the integration of digital tools, including artificial intelligence, in promoting critical thinking. Additionally, it explores how institutional policies, cultural contexts, and disciplinary differences shape students’ critical thinking dispositions and learning outcomes. Using PRISMA guidelines, 50 empirical studies from 2016 to 2025 were selected across multiple databases. The review analyzed both qualitative and quantitative research on critical thinking development, assessment techniques, AI integration, pedagogical methods, and socio-cultural influences. Findings indicate that active learning, interdisciplinary instruction, and AI-enhanced tools support critical thinking development. However, over-reliance on standardized assessments and AI-generated content can hinder deep engagement. Disciplinary and cultural factors also shape critical thinking skills. Most studies used cross-sectional designs and focused on specific disciplines or regions, limiting generalizability. Future research should explore longitudinal impacts and cross-cultural comparisons. Universities should adopt blended assessment methods, invest in AI literacy, and revise curricula to foster critical thinking through interdisciplinary and student-centered learning environments.